Sex-Specific Thresholds of High-Sensitivity Troponin in Patients With Suspected Acute Coronary Syndrome - Lee, Kuan Ken (J Am Coll Cardiol, 2019)
BACKGROUND: Major disparities between women and men in the diagnosis, management, and outcomes of acute coronary syndrome are well recognized. OBJECTIVES: The aim of this study was to evaluate the impact of implementing a high-sensitivity cardiac troponin I assay with sex-specific diagnostic thresholds for myocardial infarction in women and men with suspected acute coronary syndrome. METHODS: Consecutive patients with suspected acute coronary syndrome were enrolled in a stepped-wedge, cluster-randomized controlled trial across 10 hospitals. Myocardial injury was defined as high-sensitivity cardiac troponin I concentration >99th centile of 16 ng/l in women and 34 ng/l in men. The primary outcome was recurrent myocardial infarction or cardiovascular death at 1 year. RESULTS: A total of 48,282 patients (47% women) were included. Use of the high-sensitivity cardiac troponin I assay with sex-specific thresholds increased myocardial injury in women by 42% and in men by 6%. Following implementation, women with myocardial injury remained less likely than men to undergo coronary revascularization (15% vs. 34%) and to receive dual antiplatelet (26% vs. 43%), statin (16% vs. 26%), or other preventive therapies (p < 0.001 for all). The primary outcome occurred in 18% (369 of 2,072) and 17% (488 of 2,919) of women with myocardial injury before and after implementation, respectively (adjusted hazard ratio: 1.11; 95% confidence interval: 0.92 to 1.33), compared with 18% (370 of 2,044) and 15% (513 of 3,325) of men (adjusted hazard ratio: 0.85; 95% confidence interval: 0.71 to 1.01). CONCLUSIONS: Use of sex-specific thresholds identified 5 times more additional women than men with myocardial injury. Despite this increase, women received approximately one-half the number of treatments for coronary artery disease as men, and outcomes were not improved. (High-Sensitivity Troponin in the Evaluation of Patients With Acute Coronary Syndrome [High-STEACS]; NCT01852123).